Annealing induced transformations in structural and optical properties of Ge30Se70−xBix thin films. (3rd August 2019) - Aparimita, Adyasha; Naik, R.; Sripan, C.; Ganesan, R.
ABSTRACT: Thin films of Ge30 Se70− x Bi x ( x  = 5, 15, 20) were prepared by thermal evaporation method on glass substrates with thickness 800 nm. The films were annealed at 250°C and 320°C for 2 h to study the annealing-induced structural and optical change. The X-ray diffraction characterization revealed the amorphous to crystalline phase transformation with annealing. The indirect optical band gap decreased with annealing which is explained on the basis of phase transformation and density of localized states. The formation of surface dangling bonds around the crystallites during crystallization process reduced the band gap. The Tauc parameter and Urbach energy change show the degree of chemical disorderness in the films. The transmitivity decreased while the absorption coefficient increased with the annealing process. The microstructural study done by Field emission scanning electron microscopy shows the formation of crystallites upon annealing. Atomic force microscopy investigation on these films shows the influence of annealing on surface topography.